Hadith #2300 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Hudhayfa al-Nahdi موسى بن مسعود أبو حذيفة النهدي; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ata' bin Abi Rabah عطاء بن أبي رباح; Shabl bin 'Aabad al-Makki شبل بن عباد المكي (Sunan Abi Dawud)
“Should I return to my people, for he did not leave any dwelling house of his own and maintenance for me? She said: The Messenger of Allah (ﷺ) replied: Yes. She said: I came out, and when I was in the apartment or in the mosque, he called for me, or he commanded (someone to call me) and, therefore, I was called. He said: what did you say? So I repeated my story which I had already mentioned about my husband. Thereupon he said: Stay in your house till the term lapses. She said: So I passed my
Grade: Sahih

Hadith #4412 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Hudhayfa al-Nahdi موسى بن مسعود أبو حذيفة النهدي; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Mujahid bin Jabir مجاهد بن جبر; Shabl bin 'Aabad al-Makki شبل بن عباد المكي (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: When a slave steals, sell him, even though it be for half an uqiyah.
Grade: Hasan